(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
Resnais’s Last Year at Marienbad is considered one of the indisputable classics of modern cinema due to the series of technical, structural and narrative innovations it introduces, even so, a disturbing dimension of his was not fully addressed by specialized critics Only through feminist studies was it possible to begin to resignify what was hidden by the elegant and abstract formalism constructed by Robbe-Grillet and Resnais. In this sense, our reading starts from Higgins’ classic reading of Marienbad as an unconsciously phallocentric film, in which it is narrated the story of a rape and its subsequent cover-up; however, our hypothesis holds that Robbe-Grillet deliberately constructs an ambiguous device to maliciously subvert all knowledge. In this way, the consideration of Robbe-Grillet’s texts as hermeneutic “traps” thus opens a path of analysis that allows revealing novel elements to the film. Our work therefore proposes a comparative reading of Robbe-Grillet’s cine-roman and Resnais’s film to analyze the ways in which the former immanently plots to disavow the authorial figure of the latter and introduce confusion in the reader/spectator.